Cassia alata and its phytochemicals: a promising natural strategy in wound recovery - Keng, Jing Wen; Lee, Sue Kei; Sang, Sze Huey; Liew, Kai Bin; Teo, Swee Sen; Shaik Mohamed Mossadeq, Wan Mastura; Chow, Sek Chuen; Akowuah, Gabriel Akyirem; Lee, Siew Keah; Mai, Chun Wai; Chew, Yik Ling (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Cassia alata, a traditional herb with a global presence, is renowned for its anti‑inflammatory, antibacterial, and antifungal properties, making it a go‑to remedy for skin ailments. While it has demonstrated wound healing capabilities in both in vitro and in vivo studies, the precise mechanisms remain elusive. This review aims to highlight its key phytochemicals, their effects, and the mechanism of action. The compounds that have been reviewed and discussed include kaempferol, apigenin, quercetin, rhein, and rutin. These polyphenols play important roles in normal and impaired wound healing processes, encompassing hemostasis, inflammation, proliferation, and tissue remodeling.